Corrosion Behavior of Structural Materials for Potential Use in Nitrate Salts Based Solar Thermal Power Plants. Issue 8 (11th August 2017) - Summers, Kodi L.; Chidambaram, Dev
Abstract : Commercial and economic success of concentrated solar power (CSP) plants requires operating at maximum efficiency and capacity which necessitates the use of materials that are reliable at high temperatures. This study investigates the corrosion behavior of structural alloys in molten nitrate salts at three temperatures common to CSP plants. Corrosion behavior was evaluated using gravimetric and inductively-coupled plasma optical emission spectroscopy (ICP-OES) analysis. Surface oxide structure and chemistry was characterized using X-ray diffraction and Raman spectroscopy. Electrochemical behavior of candidate structural alloys Alloy 4130, austenitic stainless steel 316, and super-austenitic Incoloy 800H was evaluated using potentiodynamic polarization characteristics. Gravimetric and ICP-OES analysis indicated that Alloy 4130 exhibited the least corrosion resistance at 500°C compared to SS316 and 800H. However, at 300°C, the three alloys exhibited similar weight gain. Electrochemical evaluation of these candidate materials was observed to correlate well with the corrosion behavior observed from gravimetric and ICP-OES analysis. This study identifies that all three alloys exhibited acceptable corrosion rate in 300°C molten salt, while elevated salt temperatures require the more corrosion resistant alloys, stainless steel 316 and 800H. Characterization of the sample surfaces revealed the presence of spinels at lower temperatures, while Fe2 O3 was the dominant iron oxide at higher temperatures for each alloy.